97+(7x+27)=180

Simple and best practice solution for 97+(7x+27)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 97+(7x+27)=180 equation:



97+(7x+27)=180
We move all terms to the left:
97+(7x+27)-(180)=0
We add all the numbers together, and all the variables
(7x+27)-83=0
We get rid of parentheses
7x+27-83=0
We add all the numbers together, and all the variables
7x-56=0
We move all terms containing x to the left, all other terms to the right
7x=56
x=56/7
x=8

See similar equations:

| 8(x+2)-6=-5(x+2)+3 | | 1/6(2x+5)=10 | | 8(x+2)-6=-(5)(x+2)+(3) | | 3(5x+9)=25 | | (15x-60)=(10x-15) | | -11/19x=12 | | 3(u+3)-6u=12 | | 22(g-1)=2g+18 | | 17=6m+3m*2 | | (13(12)-92)+z=180 | | 5x/6-2/3=-4 | | 2x*2=6x | | F(x)=(2x+18)/x | | 17m=3m+3(m-3) | | 3x/10=4/5 | | 17m=3m+3m | | 17m=3m-3 | | (5(12)+56)=z | | (13x-92)+(5x+56)=180 | | 6x-10=-35 | | 5x+100=x | | 4x-7+8x=9x+42-4x | | 10+z=180 | | (5x+56)=(11x-4) | | 3(2x-1)-2=2(x-7)+1 | | 3×-6=7x-10 | | (16x+13)=(-20x-23) | | 3x+10-2=70 | | 3t^2+10=4t | | 3t^+10=4t | | 4(x-1)+3(x-2)=4-5x | | -18.5/x=7.4 |

Equations solver categories